Penerapan Buerger Allen Exercise terhadap Nilai Capillary Refill Time (CRT) pada Klien Diabetes Melitus Tipe 2 - Silvia Saputri; Asih Minarningtyas; Indah Puspitasari (Jurnal Gema Keperawatan, 2023)
Peripheral artery disease is more common in people with diabetes. This chronic complication leads to disruption of peripheral blood vessel flow, thus raising the problem of the ineffectiveness of peripherial tissue perfusion Epidemiological evidence suggests a link between diabetes mellitus and an increased prevalence of perifer arterial disease. Capillary refill time (CRT) is performed quickly on the base area of the nail to monitor dehydration and the amount of blood flow to the tissue.  Objectives The study of this case study to obtain an overview of the Buerger Allen Exercise Movement on Capillary Refill Time (CRT) values in patients with type 2 diabetes. Research design used with a case study approach (single case) by expressing the results of observations and documentation on the value of Capilarry Refill Time after the client performed the Buerger Allen Exercise. Subject in this case study there are 5 patients with diabetes mellitus type 2 who do not have foot injuries and are willing to do buerger movement allen exercise in the work area of UPTD Puskesmas Bekasi Jaya. After the client performed the Buerger Allen exercise for 6 days in a row for 18 minutes each day, the result of the change occurred before and after the Buerker Allen exercise, the capillary refill time was shortened in the type 2 diabetes client. For patients with type 2 diabetes mellitus can perform buerger allen exercise independently and effectively against the effectiveness of peripheral tissue perfusion showing changes in capillary refill time values. (CRT).